PENGARUH PENDEKATAN SCIENCE, TECHNOLOGY, AND SOCIETY TERHADAP KETERAMPILAN PROSES SAINS SISWA MATERI SUMBER DAYA ALAM KELAS IV SDN 173110 HUTARAJA - Debora Falensia Hutahaean; Nurhairani; Laurensia Masri Perangin Angin; Suyit Ratno; Syahrial (STKIP Subang, 2026)
This study aimed to determine the effect of the Science, Technology, and Society approach on fourth-grade students’ science process skills in the topic of Natural Resources at SDN 173110 Hutaraja. The study employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 26 students selected through saturated sampling. The research instrument was an essay-based science process skills test that had been validated and tested for reliability. Data were analyzed using normality testing and the Paired Sample t-Test. The results showed that the average science process skills score increased from 48.38 in the pretest to 81.42 in the posttest. The Paired Sample t-Test yielded a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating that the Science, Technology, and Society approach had a significant effect on students’ science process skills. Therefore, the Science, Technology, and Society approach has a positive and significant effect on students’ science process skills.